Termografia como técnica auxiliar na identificação de mastite subclínica - Costa, Lucas Batista Saraiva da (2019)
This study aimed to evaluate the use of infrared thermography as a tool to assist in the diagnosis of cow mastitis in commercial production conditions. Udder thermograms of 16 Holstein x Gir crossbred cows (450 ± 32 kg) were recorded twice a day for 3 days, one in the morning at the milking parlor (04h:00min) and another in the afternoon (13h:00min) at the barn. Milk samples were collected for somatic cell count (SCC). The degree of correlation between udder surface temperatures and somatic cell count was evaluated using Pearson's linear correlation coefficient (r) and quadratic regressions were obtained in order to verify the relationship between two variables. Infrared thermography was sensitive to changes in SCC showing its potential for subclinical mastitis detection, but the time of collection and farm management influenced the results of the thermograms. Udder surface temperatures obtained in the barn were not significantly correlated with SCC, on the other hand, temperatures obtained in the milking parlor had a significant correlation with SCC. The regression equation using the average surface temperatures of the anterior and posterior quarters at the milking time (04h:00min) obtained the best result, proving that the anterior quarters should also be considered when searching formastitis by infrared thermography.